2010
DOI: 10.4161/cc.9.17.12719
|View full text |Cite
|
Sign up to set email alerts
|

Rem2 GTPase controls proliferation and apoptosis of neurons during embryo development

Abstract: We have recently found that Rem2 GTPase, highly expressed in human embryonic stem cells (hESC), maintains the cell cycle and controls proper differentiation towards ectoderm, suggesting a role in neuronal development. We describe here the use of the zebrafish (Danio rerio) model to determine the physiological significance of Rem2 during embryogenesis. We show that Rem2 RNA is highly expressed in zebrafish embryos up to 2 hours of development followed by a decrease in expression until 48 hours when afterwards R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…First, genes encoding putative orthologs of Gem, Rad, Rem1, and Rem2 were readily identified in the Danio rerio genome. Second, transcripts for some RGK proteins have been verified and their function inferred from knockdown or screening studies [23], [32], [33]. Third, functional expression of zebrafish cDNAs in mammalian cell lines has been demonstrated [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, genes encoding putative orthologs of Gem, Rad, Rem1, and Rem2 were readily identified in the Danio rerio genome. Second, transcripts for some RGK proteins have been verified and their function inferred from knockdown or screening studies [23], [32], [33]. Third, functional expression of zebrafish cDNAs in mammalian cell lines has been demonstrated [34].…”
Section: Resultsmentioning
confidence: 99%
“…In non-mammalian vertebrates, RGK proteins also influence neuronal development. Inhibition of Rem2 expression in embryonic Danio rerio (zebrafish) interfered with midbrain development at 36 hours post fertilization [23]. Finally, a differential display screen in the urodele amphibian Cynops pyrrhogaster (Japanese fire belly newt) to identify proteins involved in limb regeneration revealed that Rad was highly up-regulated in skeletal muscle at the site of amputation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Rad was first discovered as a protein over-expressed in skeletal muscle of type II diabetic humans [1]; Gem as a mitogen-induced gene in human T cells [2]; Rem was originally cloned using a degenerate PCR strategy based on similarity to Rad and Gem [3]; and Rem2 was cloned from a rat brain cDNA library [4]. Functionally, individual RGKs have been linked to diverse functions in different cell types and tissues including (but not limited to): promotion of cell shape remodeling via regulation of cytoskeletal dynamics (Gem) [5-9]; induction of apoptosis in cardiac myocytes (Rad) [10]; regulation of synapse development and dendritic morphology (Rem2) [11, 12]; control of neuronal proliferation and apoptosis during embryogenesis, and survival of human embryonic stem cells (Rem2) [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Rem2 overexpression drove induced pluripotent stem cells (iPSCs) towards an ectodermal cell fate [81]. This role for Rem2 in neuronal precursor proliferation and neuronal development was confirmed in a later experiment in zebrafish embryos [82]. …”
Section: Rgk Proteins In the Nervous Systemmentioning
confidence: 99%